High tree diversity exposed to unprecedented macroclimatic conditions even under minimal anthropogenic climate change - Coline C. F. Boonman; Selwyn Hoeks; Josep M. Serra-Diaz; Wen-Yong Guo; Brian J. Enquist; Brian Maitner; Cory Merow; Jens-Christian Svenning (Proceedings of the National Academy of Sciences, 2025)
Tree species worldwide face increasing exposure to unprecedented macroclimatic conditions due to anthropogenic climate change, which may trigger biome shifts and ecosystem disruptions. We quantified climate change exposure–shifts to species’ currently unoccupied climate zones–for 32,089 tree species globally by 2100, assessing both species-level and local tree diversity risks. On average, 69% of species are predicted to experience macroclimatic shifts in at least 10% of their range, while 14% face exposure in over 50% of their range under a high-emission (4 °C warming) future scenario. This suggests that most species retain substantial climate refugia within their current range. However, local tree diversity exposure is predicted to be severe in vast regions, including Eurasia, the northwestern United States and Canada, northern Chile, and the Amazon Delta. Under a moderate (2 °C warming) scenario, high tree diversity exposure is mostly restricted to taiga regions in the Northern Hemisphere. These findings provide conservative estimates of climate-driven biodiversity risk, as our approach focuses solely on macroclimate and does not account for additional stressors such as land-use change or species interactions. Identifying tree species and areas of high macroclimatic shift exposure allows for targeted conservation strategies, including species stability monitoring, assisted migration, and the protection of climate refugia. Our results offer a foundation for prioritizing conservation actions in a rapidly changing climate, ensuring long-term ecosystem resilience.